Social Networks in the History of Innovation and Invention - Moon, Francis C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book integrates history of science and technology with modern social network theory. Using examples from the history of machines, as well as case studies from wireless, radio and chaos theory, the author challenges the genius model of invention. Network analysis concepts are presented to demonstrate the societal nature of invention in areas such as steam power, internal combustion engines, early aviation, air conditioning and more. Using modern measures of network theory, the author demonstrates that the social networks of invention from the 19th and early 20th centuries have similar characteristics to modern 21st C networks such as the World Wide Web. The book provides evidence that exponential growth in technical innovation is linked to the growth of historical innovation networks.
Preface and Acknowledgements -- Chapter 1 Introduction: James Watt$1 (Bs Social Network -- Chapter 2 Networks in the Machine Age: From Leonardo to Clocks to Reuleaux -- Chapter 3 Social Networks of the Internal Combustion Engine and Automobile -- Chapter 4 Social Networks in Early Aviation History -- Chapter 5 Wireless and Radio Electronics Social Networks -- Chapter 6 Social Networks in Nonlinear Dynamics, Chaos and Fractals -- Chapter 7 -- Subject Index -- Author Index.s
Keywords: Engineering; Science -- History; Physics; Social sciences -- Methodology; Engineering; Machinery and Machine Elements; History of Science; Complexity; Methodology of the Social Sciences